2012
DOI: 10.2176/nmc.52.594
|View full text |Cite
|
Sign up to set email alerts
|

Spindle Cell Oncocytoma of the Adenohypophysis With Marked Hypervascularity

Abstract: A 68-year-old male presented with a very rare case of spindle cell oncocytoma (SCO), a recently identified very rare neoplasm of the anterior pituitary, manifesting as panhypopituitarism and visual field defect. The pituitary tumor with suprasellar extension was only partially resected via transsphenoidal surgery because of the tumor consistency and bleeding. Histological diagnosis was consistent with schwannoma. The tumor regrew and angiography revealed hypervascularity, so a transcranial approach was employe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 9 publications
0
27
0
2
Order By: Relevance
“…However, case reports emerging since WHO 2007 indicate that recurrences may be even more frequent than with subtotally resected pituicytomas, although the tendency to report adverse or unusual outcomes obviously can skew the literature. Cases reported by Demssie et al , Coiré et al , Borota et al , Kloub et al , Matyja et al , Fujisawa et al and Borges et al have all had recurrences, some within 5 , 9 or 18 months' time, but most over several years , or even as long as after a 16‐year interval . Whether this suggests that spindle cell oncocytoma might deserve a higher WHO grade than I is conjectural at this point.…”
Section: Pituicytomamentioning
confidence: 71%
See 2 more Smart Citations
“…However, case reports emerging since WHO 2007 indicate that recurrences may be even more frequent than with subtotally resected pituicytomas, although the tendency to report adverse or unusual outcomes obviously can skew the literature. Cases reported by Demssie et al , Coiré et al , Borota et al , Kloub et al , Matyja et al , Fujisawa et al and Borges et al have all had recurrences, some within 5 , 9 or 18 months' time, but most over several years , or even as long as after a 16‐year interval . Whether this suggests that spindle cell oncocytoma might deserve a higher WHO grade than I is conjectural at this point.…”
Section: Pituicytomamentioning
confidence: 71%
“…Several of the uncommon clinical and biological features mentioned earlier for pituicytoma are, however, shared with spindle cell oncocytoma, including occasional association with other endocrine abnormalities in the same patient and tendency for bleeding or high vascularity . One of the original five patients reported by Roncaroli et al had an oncocytic thyroid adenoma , and the case reported by Borges et al had thyroid disease .…”
Section: Pituicytomamentioning
confidence: 99%
See 1 more Smart Citation
“…SCO is a rare entity, described first in 2002 with few subsequent case reports to date . As described first by Roncaroli et al , SCO occurs most commonly in middle and older age groups with mean age of 61.6 years .…”
Section: Discussionmentioning
confidence: 97%
“…Spindle cell oncocytoma of the adenohypophysis is a rare and diagnostically challenging entity with only twenty-four cases reported in the English literature since the first account in 2002 by Roncaroli et al, (Alexandrescu, Brown, Tandon, & Bhattacharjee, 2012;Borges, Lillehei, & KleinschmidtDeMasters, 2011;Borota et al, 2009;Coire, Horvath, Smyth, & Kovacs, 2009;Dahiya et al, 2005;Demssie et al, 2011;Farooq, Bhatt, & Chang, 2008;Fujisawa et al, 2012;Fuller, Scheithauer, Roncaroli, & Wesseling P, 2007;Kloub, Perry, Tu, Lipper, & Lopes, 2005;Matyja et al, 2010;Mlika et al, 2011;Ogiwara, Dubner, Shafizadeh, Raizer, & Chandler, 2011;Romero-Rojas et al, 2011;Roncaroli et al, 2002;Singh et al, 2012;Vajtai, Sahli, & Kappeler, 2006). The classical histologic description of SCO is that of a fascicular neoplasm arising from the adenohypophysis and composed of spindled and epithelial oncocytic cells with immunohistochemical positivity for S100, vimentin, EMA, galectin-3, and antimitochondrial antibodies (Roncaroli et al, 2002).…”
Section: Discussionmentioning
confidence: 99%